An Analysis of Trafficking Receptors Shows that CD44 and P-Selectin Glycoprotein Ligand-1 Collectively Control the Migration of Activated Human T-Cells - Ali, Amal J.; Abuelela, Ayman F.; Merzaban, Jasmeen S. (Frontiers in Immunology, 2017)
Selectins guide the traffic of activated T-cells by mediating their tethering and rolling onto inflamed endothelium, acting as beacons to help navigate them to sites of inflammation. Here, we present a comprehensive analysis of E-selectin ligands expressed on activated human T-cells. We identified several novel glycoproteins that may act as E-selectin ligands, and focus our study on comparing the role PSGL-1 (P-selectin glycoprotein ligand-1) and CD43, known E-selectin ligands, to CD44, a ligand not previously described as an E-selectin ligand on activated human T-cells. We showed that CD44 expressed on both CD4+ and CD8+ T-cells acts as a functional E-selectin ligand and thus carries a binding epitope identifying it as HCELL (hematopoietic cell E-/L-selectin ligand). Furthermore, by knocking down these ligands individually or together in primary activated human T-cells, we demonstrated that CD44, and not CD43, co-operates with PSGL-1 as major E-selectin ligands. Additionally, we confirmed the relevance of our findings to chronic autoimmune disease, by showing that CD44 and PSGL-1, but not CD43, from T-cells isolated from psoriasis patients, bind E-selectin.